Improvement of voltage profile for large scale power system using soft computing approach - Muhammad Abdillah; Herlambang Setiadi; Danang Sulistyo (Universitas Ahmad Dahlan, 2020)
In modern power system operation and planning, reactive power is an important part of power system operation to supply electrical load such as an electric motor. However, the reactive current that flows from the generator to load demand can cause voltage drop and active power loss. Hence, it is essential to install a compensating device such as a shunt capacitor close to the load bus to reduce the total power loss of the transmission line and improve the voltage stability of the system. This paper presents the application of a genetic algorithm (GA), particle swarm optimization (PSO), and artificial bee colony (ABC)) to obtain the optimal size of the shunt capacitor where those capacitors are located on the critical bus. To examine the efficacy of the proposed algorithm, Java-Madura-Bali (JAMALI) 500kV power system grid is used as the test system. From the simulation results, the use of PSO and ABC algorithms to obtain the sizing of the capacitor’s capacity can reduce the power loss of around 15.873 MW. Moreover, a different result is showed by the GA approach where the power loss in the JAMALI 500kV power grid can be compressed only up to 15.54 MW or 11.38% from the power system operation without a shunt capacitor. The three soft computing techniques could also maintain the voltage profile within 1.05 p.u and 0.95 p.u.